Diabetes mellitus and risk of pancreatic cancer in China: A meta-analysis based on 26 case-control studies. Issue 3 (June 2019) - Zhang, Ji-Jun; Jia, Jie-peng; Shao, Quan; Wang, Ying-kai
Highlights: The relation between diabetes mellitus and pancreatic cancer risk from many publications concluded inconsistent results. Whether the association differs between populations from different ethnic backgrounds remains unknown. This meta-analysis assessed the relationship between diabetes mellitus and risk of pancreatic cancer in China. The subgroup analysis with respect to geographic area and control sources was performed. This study included a larger number of studies which were conducted in Chinese populations. Abstract: Aims: The relationship between diabetes mellitus and pancreatic cancer risk from is uncertain based on the results of existing publications. The current report updated and re-evaluated the possible association between diabetes mellitus and pancreatic cancer risk in China. Methods: Six databases (PubMed, Embase, Web of Science, the Cochrane Library, the Chinese Biomedical Database, and the Chinese National Knowledge Infrastructure) were used for the literature search up to October 2017. Results: Twenty-six case-control studies involving 7702 pancreatic cancer cases and 10186 controls were screened out. The overall summary estimate for the relationship between diabetes and pancreatic cancer was 3.69 (95% CI, 3.12–4.37). The subgroup analysis indicated positive associations among northern and southern Chinese, as well as studies with healthy population or hospital controls. In addition, the risk of developing pancreatic cancer was inversely associated with the duration of diabetes, with the highest risk of pancreatic cancer occurring among patients with diabetes <2 years. Individuals who had diabetes <2 years had a >2-fold higher risk of developing pancreatic cancer than individuals who had diabetes for 2–4 years or 5–10 years (OR, 4.92; 95% CI, 4.16–5.80 vs. OR, 1.92; 95% CI, 1.30–2.85/OR, 2.14; 95% CI, 1.49–3.09). Conclusions: This meta-analysis strongly supports that an association exists between diabetes and an increased risk of pancreatic cancer in China, which should be confirmed with other ethnic groups.